Part 1:
Step 1:
Find the value of G(16)
Using the equation for g(x) =√x, replace x with 16 and solve:
g(16) = √16 = 4
Step 2:
Now using the answer for g(16) replace x in the equation fir f(x) with 4 and solve:
f(x) = x +2
f(4) = 4+2 = 6
Part 2:
following the same steps as part 1:
f(g(x)) would be replacing x in the equation ofr f(x)with the equation for g(x)
f(g(x)) = √x +2
Answer:
(9,5)
Step-by-step explanation:
10+8/2=18/2=9
6+4/2=10/2=5
Answer:
x = -10
y = -13
Step-by-step explanation:
-6(y + 3) + 4y = 8
-6y - 18 + 4y = 8
-2y - 18 = 8
+ 18 + 18
-2y (÷ -2) = 26 (÷ -2)
y = -13
x = -13 + 3
x = -10
The answer to this equation is 1412 or 21-15